MODEL PEMASARAN KEWIRAUSAHAAN MELALUI DIGITAL MARKETING SEBAGAI PEMODERASI UNTUK MENINGKATKAN KINERJA PENJUALAN UMKM KOTA SEMARANG - Heru Sri Wulan; Feri Agustina; Cicik Harini (ITB AAS INDONESIA Surakarta, 2021)
The emergence of the corona virus in 2020 has devastated the economy in Indonesia, making the strength of MSMEs re-examined. The decline in turnover in the non-culinary sector reached 30-35% due to restrictions on activities that made it difficult for business actors to make face-to-face sales. Therefore, SMEs must be able to master digital marketing. Utilizing the marketing concept through the use of digital technology, it is hoped that MSMEs will be able to develop and become the center of economic power. The current era of technology is indeed unavoidable, through digital marketing it is possible for MSME actors to market their products online, offer and make online banking system payment transactions. This study aims to analyze the entrepreneurial marketing model through digital marketing as a moderating variable in improving sales performance. in MSMEs in Semarang City. The population in this study were MSME actors who were registered at the Cooperatives and MSMEs Service in the city of Semarang. The sampling technique used by the author in conducting this research is using simple random sampling, namely taking samples from the population randomly, using the Slovin formula, obtained 98 samples. The method of data analysis was carried out by testing instrument validity and reliability, testing classical assumptions, testing hypotheses and testing moderating variables using MRA (Moderated Regression Analysis). The results showed a positive and significant influence on entrepreneurial marketing in increasing the sales volume of MSMEs in Semarang City, but the effect of digital marketing as a moderating on sales volume in the first output had a significant effect and the interaction effect on the second output had no significant effect, meaning digital marketing as a moderating variable in the relationship between the method of marketing performance is a predictor moderator. Keywords: Entrepreneurship Marketing, Digital marketing, Sales volume, MSMEs.